Pengalaman Belajar Siswa SMP Negeri 02 Ella Hilir dalam Pengembangan Keterampilan Shooting Sepak Bola Melalui Strategi Fun Games Target Challenge - Rizki Setiawan; Eko Rudiansyah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze students’ learning experiences in developing shooting skills in football through the implementation of the Fun Games Target Challenge strategy among eighth-grade students at SMPN 02 Ella Hilir. This research used a phenomenological approach with a qualitative descriptive method. The participants consisted of 18 students, including 11 male students and 7 female students. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted using thematic analysis through coding, theme categorization, and data interpretation. The validity of the data was ensured through source triangulation and member checking. The results of the study show that the implementation of the Fun Games Target Challenge strategy provides positive learning experiences for students. Students demonstrated high enthusiasm, motivation, and participation during the learning process. The game-based learning approach made students more active, confident, and better able to understand shooting techniques because it was conducted in a fun and challenging atmosphere. In addition, the results of observations and interviews indicate an improvement in shooting skills, shown by increased shooting accuracy, movement coordination, and the ability to direct the ball toward the target. This strategy also encourages good cooperation among students and increases their engagement in physical education learning. Therefore, the Fun Games Target Challenge strategy can be an effective alternative learning approach to improve football shooting skills while creating a meaningful and enjoyable learning experience for students. Keywords: Fun Games Target Challenge, shooting in football, learning experience, physical education, motor skills, game-based learning